Control of Large Wind Energy Systems for Acoustic Noise Reduction by Using Multi-Objective Optimal Control - Rivarola, Dora Fanny Andrea (2023)
An important restriction to the social acceptance of the wind energy systems is the acoustic noise that they introduce into the environment, particularly during the night hours in settlements close to the wind farms. This problem is solved by reducing the rotational speed of the machines with a corresponding power loss. The usual way to do this is to switch the set point of the rotor speed between day and night operations. The present contribution studies the problem and proposes two control system configurations that try to minimize the power losses by tracking and adjusting the rotational speed. The concept is based on two controllers working cooperatively. The controller tuning is carried out by using a game-theoretic approach solved by multi-objective optimization. The simulation results show an improvement with respect to the common procedure, such that it looks promising for the application to real machines.